Earnings Differences among Senior University Administrators: Evidence by Gender and Academic Field - Mang, Colin F. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
This study examines earnings inequality by gender and academic field among senior university administrators, including presidents, vice presidents, associate and assistant vice presidents, and deans, using data from the Canadian province of Ontario. While a 4.4 percent earnings gap between male and female administrators is initially identified, much of the gap is explained by earnings inequality across academic fields and by the career experience of the administrators. Administrators who specialize in professional fields such as engineering, health sciences, law, and social work earn between 12 percent and 33 percent more than administrators who specialize in liberal fields in the humanities and social sciences.